2010
DOI: 10.1021/ja104229a
|View full text |Cite
|
Sign up to set email alerts
|

Hydrido-Ruthenium Cluster Complexes as Models for Reactive Surface Hydrogen Species of Ruthenium Nanoparticles. Solid-State 2H NMR and Quantum Chemical Calculations

Abstract: The (2)H quadrupolar interaction is a sensitive tool for the characterization of deuterium-metal binding states. In the present study, experimental solid-state (2)H MAS NMR techniques are used in the investigations of two ruthenium clusters, D(4)Ru(4)(CO)(12) (1) and D(2)Ru(6)(CO)(18) (2), which serve as model compounds for typical two-fold, three-fold, and octahedral coordination sites on metal surfaces. By line-shape analysis of the (2)H MAS NMR measurements of sample 1, a quadrupolar coupling constant of 67… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 57 publications
5
42
0
Order By: Relevance
“…Poteau et al [38] studied spectroscopic and thermodynamic properties of surfacic hydrides on Ru (0001) model surface: the influence of the coordination modes and the coverage by density functional theory and this study partially opens the route to DFT studies of multistep hydrogenation reactions at the surface of ruthenium nanoparticles monitored by spectroscopic techniques. Torsten Gutmann et al [39] studied hydrido-ruthenium cluster complexes as models for reactive surface hydrogen species of ruthenium nanoparticles by solid-state 2 H NMR and quantum chemical calculations and found that the 2 H nuclear quadrupolar interaction is a sensitive tool for distinguishing the binding state of the deuterons to the transition metal.…”
Section: Introductionmentioning
confidence: 99%
“…Poteau et al [38] studied spectroscopic and thermodynamic properties of surfacic hydrides on Ru (0001) model surface: the influence of the coordination modes and the coverage by density functional theory and this study partially opens the route to DFT studies of multistep hydrogenation reactions at the surface of ruthenium nanoparticles monitored by spectroscopic techniques. Torsten Gutmann et al [39] studied hydrido-ruthenium cluster complexes as models for reactive surface hydrogen species of ruthenium nanoparticles by solid-state 2 H NMR and quantum chemical calculations and found that the 2 H nuclear quadrupolar interaction is a sensitive tool for distinguishing the binding state of the deuterons to the transition metal.…”
Section: Introductionmentioning
confidence: 99%
“…Getting knowledge of their structure would be very helpful, but their structure may often not be characterized at the same level as well-defined molecular species. [8][9][10] The coordination of hydrogen to metal nanoparticles synthesized by organometallic techniques is especially important. 7 In most cases, spectra assignment is not obvious, so that there is a need for providing reference data.…”
Section: Introductionmentioning
confidence: 99%
“…Although in all these low-energy structures hydride atoms adopt edge-bridging or face-capping positions, it is possible to study terminal positions in geometries with higher energy as well as subsurfacic hydrides in tetrahedral or octahedral sites. 10,18 Nevertheless, the wide chemical shift range observed for a given coordination mode does not allow us to make safe assignations, unless theoretical calculations are involved. 19,20 Tetrahedral and octahedral structures belong, respectively, to the nido and closo family of clusters, so that Ru 4 and Ru 6 clusters obeying the rules should exhibit 60 and 86 valence electrons.…”
Section: Introductionmentioning
confidence: 99%
“…Over Ru metal surfaces, hydrogen can be adsorbed on a single-atom site, two-fold site and also threefold hollow site. However, the lowest adsorption energy allowing hydrogen activation has been found for the three-fold hollow site, which may be of the type fcc (on the surface) or hcp (on an octahedral subsurface site) [22,23]. On the other hand, the most active sites for N 2 dissociative adsorption are the B 5 -type sites, exposing a three-fold hollow site close together with a bridge site [24][25][26].…”
Section: Analysis Of Ruo 2 Crystal Morphology By Three-dimensional Afmentioning
confidence: 99%